Determination of trace analytesin biological fluids by Q-TOF LC-MS using isotope dilution method - Er Öztürk, Elif (My University, 2020)
Determination of trace analytes brought a series of questions related to the method performance for low concentration levels in diverse matrices. As one of the relatively new developments, the isotope dilution method is a highly sensitive and selective analytical method with high precision for trace analysis. This thesis presents the determination of erectile drugs and amino acids using isotope dilution strategy. All determinations were performed with Quadrupole–Time–of–Flight Liquid Chromatography–Mass Spectrometry system. The chromatographic separation of erectile drugs including sildenafil, tadalafil, vardenafil and avanafil in urine and plasma was performed on a reversed phase column. To achieve higher sensitivity for analytes, magnetic solid phase extraction was employed and the detection limits for combined method were found to be between 0.16 – 0.94 ng g-1. In the second part of this thesis, it was focused on the selective and sensitive determination of 17 free amino acids in biological matrices. In this context, two approaches were employed including hydrophilic interaction chromatography for underivatized amino acids and reversed phase chromatography for derivatized amino acids. The detection limits were obtained between 0.03 – 2.26 μmol kg-1 and 0.016 and 0.266 μmol kg-1 for underivatized and derivatized amino acids, respectively. Accuracy and precision of developed methods were evaluated by performing recovery experiments in urine, plasma and serum samples using matrix matching strategy. Despite obtained satisfactory limits in percent recoveries, isotope dilution strategy was employed for each study to obtain quantitative results with unprecedented analytical quality (accuracy levels close to 100%). The analytical methods presented in this study provided simple and feasible routes for accurate and precise determinations of erectile drugs and amino acids in complex biological matrices. Therefore, these methods could be easily adapted for quantification of selected analytes in clinical applications which have crucial importance to diagnose and screen disorders linked to physiological levels of these analytes or to discover new biomarkers.

Herhangi bir eser analitin tayini, farklı matrislerdeki analitlerin düşük konsantrasyon seviyeleri için yöntem performansıyla ilgili bir dizi soruyu beraberinde getirmektedir. Son zamanlarda geliştirilen yeni yöntemlerden biri olan izotop seyreltme yöntemi, eser analitlerin analizi için yüksek hassasiyette, oldukça duyarlı ve seçici bir analitik yöntemdir. Bu çalışmada, erektil ilaçların ve aminoasitlerin izotopik seyreltme stratejisi kullanılarak tayin edilmeleri sunulmaktadır. Bu amaçla, analitik tayinler Kuadropol-Uçuş Zamanlı Sıvı Kromatografisi –Kütle Spektrometresi sistemi kullanılarak gerçekleştirilmiştir. Sildenafil, tadalafil, vardenafil ve avanafili kapsayan erektil ilaçlar idrarda ve plazmada ters faz yöntemi ile kromatografik olarak ayrılmıştır. Bu analitler için daha yüksek hassasiyet elde edebilmek için, Manyetik Katı Faz Ekstraksiyonu yöntemi uygulanmıştır ve kombine yöntem için tayin limitleri 0.16 –0.94 ng g-1aralığında tespit edilmiştir. Sunulan bu tezin ikinci bölümünde ise biyolojik matrislerdeki 17 serbest amino asidin seçici ve duyarlı bir yöntem ile tayin edilmesi üzerine yoğunlaşılmıştır. Bu bağlamda, türevlendirilmemiş serbest amino asitlerin tayini için hidrofilik etkileşim kromatografisi, türevlendirilmiş amino asitlerin tayini için ise ters faz kromatografisini içeren iki farklı yaklaşım üzerine çalışılmıştır. Tayin limitleri türevlendirilmemiş ve türevlendirilmiş amino asitler için sırasıyla; 0.03 –2.26 μmol kg-1ve 0.016 -0.266 μmol kg-1aralıklarında tespit edilmiştir. Geliştirilen yöntemlerin doğruluğu ve kesinliği, matris eşleştirme stratejisi kullanılarak idrar, plazma ve serum örneklerinde geri kazanım deneyleri ile değerlendirilmiştir. Yüzde geri kazanımlarda tatmin edici sınırlar içerisinde sonuçlar elde edilmesine rağmen, benzeri görülmemiş analitik kalitede kantitatif sonuçlar (%100’e yakın doğruluk) elde etmek için her çalışmada ayrıca izotop seyreltme stratejisi de uygulanmıştır. Bu çalışmada sunulan analitik yöntemler, karmaşık biyolojik matrislerde erektil ilaçların ve amino asitlerin doğru ve kesin tespiti için basit ve uygulanabilir yollar göstermektedir. Geliştirilen bu yöntemlerin klinik uygulamalarda seçilen analitlerin miktarlandırılması için uygulanması, bu analitlerin fizyolojik seviyelerine bağlı olarak ortaya çıkabilen hastalıkları teşhis etmek ve taramak, ya da bazı hastalıklar için yeni biyobelirteç olma ihtimallerini doğru değerlendirmek adına oldukça önemli bir yer tutmaktadır.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: Trace analyte Iisotope dilution; Erectile drugs; Amino acids; Biological fluids; Eser analitler; İzotop seyreltme; Erektil ilaçlar; Amino asitler; Biyolojik sıvılar